The Concept of Rehabilitation Law for Military Personnel Who Commit Narcotics Crimes in the Perspective of Legal Certainty - Salam, Abdul (Politeknik Siber Cerdika Internasional, 2025)
This study examines the provision of rehabilitation for TNI members involved in narcotics abuse, with an emphasis on a theoretical framework that includes aspects of law, criminality, rehabilitation, and human rights (HAM). Rehabilitation is recognized as a right for narcotics addicts in accordance with Law No. 35 of 2009, which emphasizes the importance of restoring health without neglecting legal responsibility. However, in practice, TNI members are often faced with dismissal sanctions without being given the opportunity to undergo rehabilitation, which creates injustice. This study uses normative juridical methods to analyze existing regulations and challenges in the implementation of rehabilitation. The results of the study show the need for harmonization between civil and military law, the establishment of special rehabilitation centers, and the strengthening of internal TNI regulations. With a holistic approach, it is hoped that rehabilitation can be an effective solution in dealing with narcotics abuse among the military, as well as strengthening the integrity of the TNI as a just institution. In addition, this study aims to analyze the setting, application, and ideal concept of rehabilitation for the military involved in narcotics crimes. Despite the laws governing rehabilitation, its implementation among the military still faces various challenges. With a qualitative approach, this research delves deeper into existing issues. The results show that although rehabilitation aims to restore the rights and dignity of soldiers, its implementation is often hampered by complex internal and external factors.